2015
DOI: 10.1007/s10571-015-0257-8
|View full text |Cite
|
Sign up to set email alerts
|

The Noncompetitive AMPAR Antagonist Perampanel Abrogates Brain Endothelial Cell Permeability in Response to Ischemia: Involvement of Claudin-5

Abstract: The blood-brain barrier (BBB) is formed by brain endothelial cells, and decreased BBB integrity contributes to vasogenic cerebral edema and increased mortality after stroke. In the present study, we investigated the protective effect of perampanel, an orally active noncompetitive AMPA receptor antagonist, on BBB permeability in an in vitro ischemia model in murine brain endothelial cells (mBECs). The results showed that perampanel significantly attenuated oxygen glucose deprivation (OGD)-induced loss of cell v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…In this study, we observed that otopathogenic P. aeruginosa induces death of human MDMs and mouse BMMϕ as determined by LDH release in the cell culture supernatants and ethidium homodimer-I staining. LDH is the most acceptable and reliable marker for determining host cell death (Kwon et al, 2015; Park et al, 2015; Lv et al, 2016) . Ethidium homodimer-I is a fluorescent nuclear stain that penetrates dead cells due to disrupted plasma membrane and increases intensity after binding to DNA (Eidet et al, 2015; McCanna et al, 2015; Yoeruek et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that otopathogenic P. aeruginosa induces death of human MDMs and mouse BMMϕ as determined by LDH release in the cell culture supernatants and ethidium homodimer-I staining. LDH is the most acceptable and reliable marker for determining host cell death (Kwon et al, 2015; Park et al, 2015; Lv et al, 2016) . Ethidium homodimer-I is a fluorescent nuclear stain that penetrates dead cells due to disrupted plasma membrane and increases intensity after binding to DNA (Eidet et al, 2015; McCanna et al, 2015; Yoeruek et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As described elsewhere [ 50 ], synaptically-activated neurons and/or astrocytes could directly stimulate brain microvessels by releasing mediators that traverse the VSMC or pericyte layers and bind to receptors located on the abluminal side of endothelium. Interestingly, brain microvascular endothelial cells may also express NMDARs [ 55 , 56 ] and mGluR1 [ 57 , 58 , 59 , 60 ], although their potential contribution to NVC has been barely appreciated [ 4 ]. Accordingly, recent studies demonstrated that endothelial NMDARs participate in glutamate-induced vasodilation of intraparenchymal arterioles by mediating Ca 2+ entry and subsequent eNOS activation [ 55 , 56 ].…”
Section: Neurovascular Couplingmentioning
confidence: 99%
“…In addition, PER has also been reported to be beneficial for patients with Parkinson’s disease and motor neuron diseases [12,13,14,15] and also in treating glioma-associated epilepsy [16,17,18,19]. However, several reports have shown that some of the actions of PER may not be closely linked to its blocking effect on AMPA receptors [11,20].…”
Section: Introductionmentioning
confidence: 99%